A kind of antibacterial and antiviral nanomaterial and its preparation method
By synthesizing a nanomaterial that is antibacterial and antiviral, the problem of insufficient functions of existing flame retardants in the combustion process is solved, and efficient flame retardant, antibacterial and antiviral effects are achieved, and it is suitable for a variety of materials.
Patent Information
- Application Number
- CN202410610558.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-16
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-05-16
AI Technical Summary
Existing flame retardants produce harmful gases during combustion and lack antibacterial and antiviral functions on textiles, making it difficult to meet environmental protection and functional requirements.
A novel structure of antibacterial and antiviral nanomaterial is used, which is synthesized by replacement reaction and catalytic action by methylphosphate, which has good flame retardant, antibacterial and antiviral effects.
After multiple cleanings, the nanomaterial still maintains an antibacterial effect of more than 90% and an antiviral effect of more than 85%. It has good physical and chemical properties, is safe and environmentally friendly, and is suitable for textiles, wood, paper and other materials.
Smart Images

Figure CN118561773B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of flame retardant preparation, and specifically relates to an antibacterial and antiviral nano material and a preparation method thereof. Background Art
[0002] With the rapid development of social economy and textile industry, the improvement of people's material and cultural living standards, the demand for civilian clothing, decoration and industrial textiles has greatly increased, and the fires caused by textile combustion have also increased. Therefore, people have gradually paid attention to the flame retardant effect of various textiles. Flame retardants used in textiles must be environmentally and labor-saving and safe, compatible with fabrics, not damaging the beauty and texture characteristics of fabrics, and must withstand a lot of washing and cleaning.
[0003] Although traditional halogen-containing flame retardants have superior performance, they are criticized for environmental issues because they produce a large amount of harmful gases during combustion. Although inorganic phosphorus flame retardants are less toxic and cheaper, their flame retardant effect is average, especially when used on flammable textiles, they often fail to achieve the expected flame retardant effect. Organic phosphorus flame retardants have good flame retardant effects, can achieve higher flame retardant levels, have less impact on the environment, do not produce harmful gases, and have good performance in safety and environmental performance.
[0004] The various textiles used in people's daily lives are a good place for various pathogenic microorganisms to live and are also an important source of disease transmission. These microorganisms will grow and multiply rapidly under suitable conditions, and spread diseases through contact, affecting human physical and mental health. Therefore, consumers have a demand for antibacterial functions in textiles. Summary of the invention
[0005] In view of the problems existing in the prior art, the present invention provides a novel antibacterial and antiviral nanomaterial having good and lasting antibacterial and antiviral effects. The present invention also provides a method for preparing the antibacterial and antiviral nanomaterial, which has the advantages of easy availability of raw materials and a simple synthesis path.
[0006] Specifically, one aspect of the present invention provides an antibacterial and antiviral nanomaterial represented by formula (I)
[0007] R-Cu-R
[0008] (I)
[0009]
[0010] Another aspect of the present invention provides a method for preparing the antibacterial and antiviral nanomaterial represented by formula (I), the preparation method comprising the following steps:
[0011] S1: performing a replacement reaction between sodium dichloroisocyanurate and cupric chloride, and obtaining cupric dichloroisocyanurate by crystallization and filtration;
[0012] S2: dissolving the copper dichloroisocyanurate described in step S1 in an ethanol aqueous solution, adjusting the pH value, and reacting under the action of a first catalyst to obtain a copper alkoxide R2-Cu-R2 of formula (C)
[0013] (C)
[0014]
[0015] S3: reacting the copper alkoxide of formula (C) described in step S2 with methylphosphoric acid filled with nitrogen in the presence of a second catalyst to obtain the antibacterial and antiviral nanomaterial of formula (I).
[0016] In one or more embodiments, the first catalyst is a substance formed by combining one or more of iridium, nickel, palladium, platinum, rhodium or ruthenium metals with activated carbon;
[0017] The second catalyst is one or more of magnesium chloride, aluminum chloride, and silicon chloride;
[0018] In step S2, the reaction temperature is 70-85°C;
[0019] In step S2, the pH value is adjusted to 5.3-6.0.
[0020] In one or more embodiments, in step S1, the mass ratio of sodium dichloroisocyanurate to cupric chloride is (1.6-2.5): (1-1.5); the reaction temperature in step S1 is 40-50°C, and the reaction time is 2-4h.
[0021] In one or more embodiments, in step S2, the volume concentration of the ethanol aqueous solution is 70% to 78%.
[0022] In one or more embodiments, the mass ratio of copper dichloroisocyanurate to the first catalyst in step S2 is 10:(3-5); the reaction temperature in step S2 is 70-85° C., and the reaction time is 2-4 hours.
[0023] In one or more embodiments, step S2 also includes recrystallization, cooling the reaction mixture obtained in step S2, adding hydrochloric acid to acidify and then filtering, dissolving the filtered product in a petroleum ether-ethanol mixed solution for recrystallization, the molar ratio of petroleum ether to ethanol is (1-1.5): (0.5-1), and the temperature of the petroleum ether-ethanol solution is 60-70°C.
[0024] In one or more embodiments, in step S2, the mass ratio of copper alkoxide of formula (C) to methyl phosphoric acid is (3.5-4.5):(9-12), the reaction temperature is 100-150° C., and the reaction time is 3-7 h.
[0025] In one or more embodiments, in step S2, the first catalyst is added in 3 to 5 equal portions within a reaction time of 1 to 3 hours.
[0026] In one or more embodiments, step S3 further comprises liquid separation and low-temperature water washing. The reaction liquid obtained in step S3 is separated to obtain an oil phase, and the oil phase is washed with low-temperature water at a temperature of 10 to 15° C. for 2 to 3 times.
[0027] Compared with the prior art, the present invention has the following advantages and effects:
[0028] The antibacterial and antiviral nanomaterials provided by the present invention have flame retardant properties, antibacterial and antiviral functions. The antibacterial and antiviral effects can reach more than 99%, and the antibacterial and antiviral effects are durable. After multiple washings, they still have more than 90% antibacterial effects and more than 85% antiviral effects. From the perspective of preparation technology, the production raw materials are easy to obtain and cheap, and the production cost is low; from the perspective of performance, this product has good physical and chemical properties, strong adhesion, can be well attached to the surface of textiles, no toxic gas is generated during flame retardancy, multifunctional (usually flame retardants only have anti-combustion but no antibacterial and antiviral functions), good light stability, non-corrosive, strong acid and alkali resistance, and good water resistance. This flame retardant can not only be used for flame retardancy of textiles, but also for flame retardancy of wood, paper, carpets, and other materials, and has good antibacterial and antiviral functions. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 A synthetic route of an antibacterial and antiviral nanomaterial according to an embodiment of the present invention;
[0030] Figure 2 A flow chart of the preparation of antibacterial and antiviral nanomaterials according to an embodiment of the present invention;
[0031] Figure 3 Infrared absorption spectrum of antibacterial and antiviral nanomaterials according to an embodiment of the present invention;
[0032] Figure 4 A graph showing the attenuation of the antibacterial efficiency of an antibacterial and antiviral nanomaterial according to an embodiment of the present invention;
[0033] Figure 5 A graph showing the attenuation of the antiviral efficiency of an antibacterial and antiviral nanomaterial according to an embodiment of the present invention. DETAILED DESCRIPTION
[0034] The following description is used to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments described below are only examples, and those skilled in the art can think of other obvious variations. The basic principles of the present invention defined in the following description can be applied to other embodiments, variations, improvements, equivalents, and other technical solutions that do not deviate from the spirit and scope of the present invention.
[0035] If no specific conditions are specified in the examples of the present invention, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. All raw materials, reagents, etc., whose manufacturers are not specified, are conventional products that can be purchased commercially.
[0036] The present invention finds that the antibacterial and antiviral nanomaterial having the structure shown in formula (I) can be used as a flame retardant and has both antibacterial and antiviral properties.
[0037] R-Cu-R
[0038] (I)
[0039]
[0040] according to Figure 1 and Figure 2 The present invention provides a method for preparing an antibacterial and antiviral nanomaterial of formula (I), comprising the following steps:
[0041] S1: performing a replacement reaction between sodium dichloroisocyanurate and cupric chloride, and obtaining cupric dichloroisocyanurate by crystallization and filtration;
[0042] S2: dissolving the copper dichloroisocyanurate described in step S1 in an ethanol aqueous solution, adjusting the pH value, and reacting under the action of a first catalyst to obtain a copper alkoxide of formula (C)
[0043] R2-Cu-R2
[0044] (C)
[0045]
[0046] S3: reacting the copper alkoxide of formula (C) described in step S2 with methylphosphoric acid filled with nitrogen in the presence of a second catalyst to obtain the antibacterial and antiviral nanomaterial of formula (I).
[0047] The first catalyst is a substance formed by combining one or more of iridium, nickel, palladium, platinum, rhodium or ruthenium metals with activated carbon; the second catalyst is one or more of magnesium chloride, aluminum chloride and silicon chloride.
[0048] Example 1
[0049] Step S1
[0050]
[0051] Weigh 16 g of sodium dichloroisocyanurate of formula (A) and 10 g of CuCl2, disperse them in deionized water, stir to dissolve, heat to 45°C and react for 3 h to obtain a suspension.
[0052] The suspension was placed in a 4°C refrigerator for crystallization, excess water was removed by filtration, and the suspension was placed in a 20°C refrigerator for 4 hours in the shade, and dried in an 80°C oven for 1 hour to obtain copper dichloroisocyanurate of formula (B).
[0053] Step S2
[0054]
[0055] Add 100 mL of anhydrous ethanol and deionized water into the reactor and maintain the temperature at 15°C. Use an alcohol density meter to test the concentration of ethanol to make it 70%.
[0056] Add 0.5 g NaOH powder, stir thoroughly, and determine the alkali concentration by acid-base titration to make the pH value around 6.0.
[0057] 10g of copper dichloroisocyanurate of formula (B) was added to the reaction kettle, stirred thoroughly, and after it was completely dissolved, heated to 70°C for 4h, and a total of 3g of the first catalyst was added in 3 times within 1.5h to obtain a reaction mixture. The first catalyst was a combination of nickel and activated carbon, and the ratio of nickel to activated carbon was 1:2.
[0058] The obtained reaction mixture was cooled to 20°C, acidified to pH 7 by adding hydrochloric acid, and filtered with suction. The filtered product was dissolved in a petroleum ether-ethanol mixed solution prepared by 1 mol of petroleum ether and 0.5 mol of ethanol at 60°C for recrystallization, and washed with 45% ethanol to obtain copper alkoxide of formula (C).
[0059] Step S3
[0060]
[0061] 7 g of the obtained copper alkoxide of formula (C) and 18 g of methylphosphoric acid were added to a reaction kettle, distilled water was added, stirred evenly, nitrogen was continuously introduced, a second catalyst was added, heated to 100°C for reaction for 7 hours, and cooled to 15°C after the reaction was completed to obtain a reaction solution. The second catalyst was a mixture of magnesium chloride and aluminum trichloride, and the ratio of magnesium chloride to aluminum trichloride was 1:1.
[0062] The obtained reaction liquid is separated to obtain an oil phase, and the oil phase is washed three times with 10° C. distilled water, separated, dehydrated, filtered, and distilled to obtain an antibacterial and antiviral nanomaterial of formula (I).
[0063] Example 2
[0064] Step S1
[0065] Weigh 20 g of sodium dichloroisocyanurate of formula (A) and 12 g of CuCl2, disperse them in deionized water, stir to dissolve, heat to 40°C and react for 4 hours to obtain a suspension.
[0066] The suspension was placed in a 6°C refrigerator for crystallization, excess water was removed by filtration, and the suspension was placed in a 17°C refrigerator for 5 hours in the shade, and dried in an oven at 75°C for 2 hours to obtain copper dichloroisocyanurate of formula (B).
[0067] Step S2
[0068] Add 100 mL of anhydrous ethanol and deionized water into the reactor and maintain the temperature at 17°C. Use an alcohol density meter to test the ethanol concentration to make it 74%.
[0069] Add 1 g of NaOH powder, stir thoroughly, and determine the alkali concentration by acid-base titration to make the pH value around 5.6.
[0070] 10 g of the prepared copper dichloroisocyanurate of formula (B) was added to the reaction kettle, stirred thoroughly, and after it was completely dissolved, heated to 75°C for reaction for 3 h, and a total of 4 g of the first catalyst was added in 4 portions within 2 h to obtain a reaction mixture. The first catalyst was a combination of palladium and activated carbon, and the ratio of palladium to activated carbon was 1:2.
[0071] The obtained reaction mixture was cooled to 22° C., acidified to pH 7.2 by adding hydrochloric acid, and filtered. The filtered product was dissolved in a petroleum ether-ethanol mixed solution prepared by 1.2 mol petroleum ether and 0.7 mol ethanol at 65° C. for recrystallization, and washed with 50% ethanol to obtain copper alkoxide of formula (C).
[0072] Step S3
[0073] 8 g of the obtained copper alkoxide of formula (C) and 20 g of methylphosphoric acid were added to a reaction kettle, distilled water was added, stirred evenly, nitrogen was continuously introduced, a second catalyst was added, heated to 120°C for reaction for 5 hours, and cooled to 17°C after the reaction was completed to obtain a reaction solution. The second catalyst was a mixture of silicon chloride and aluminum trichloride, and the ratio of silicon chloride to aluminum trichloride was 1:1.
[0074] The obtained reaction liquid is separated to obtain an oil phase, and the oil phase is washed twice with 12° C. distilled water, separated, dehydrated, filtered, and distilled to obtain an antibacterial and antiviral nanomaterial of formula (I).
[0075] Example 3
[0076] Step S1
[0077] Weigh 25 g of sodium dichloroisocyanurate of formula (A) and 15 g of CuCl2, disperse them in deionized water, stir to dissolve, heat to 50°C and react for 2 h to obtain a suspension.
[0078] The suspension in step 1 was placed in a refrigerator at 8°C for crystallization, and excess water was removed by filtration. The suspension was placed in a 15°C refrigerator for 6 hours in the shade, and dried in an oven at 70°C for 3 hours to obtain copper dichloroisocyanurate of formula (B).
[0079] Step S2
[0080] Add 100 mL of anhydrous ethanol and deionized water into the reactor and maintain the temperature at 20°C. Use an alcohol density meter to test the concentration of ethanol to make it 78%.
[0081] Add 1.5 g NaOH powder to the mixture, stir thoroughly and determine the alkali concentration by acid-base titration to make the pH value around 5.3.
[0082] 10g of the prepared copper dichloroisocyanurate of formula (B) was added to the reaction kettle, stirred thoroughly, and after it was completely dissolved, heated to 85°C for reaction for 2h, and 5g of the first catalyst was added in 5 times within 3h to obtain a reaction mixture. The first catalyst is a composite material of nickel, palladium and activated carbon, and the ratio of nickel, palladium and activated carbon is 1:1:3.
[0083] The obtained reaction mixture was cooled to 25°C, acidified to pH 7.5 by adding hydrochloric acid, and filtered. The filtered product was dissolved in a petroleum ether-ethanol mixed solution prepared by 1.5 mol petroleum ether and 1 mol ethanol at 70°C for recrystallization, and washed with 55% ethanol to obtain copper alkoxide of formula (C).
[0084] Step S3
[0085] 9 g of the obtained copper alkoxide of formula (C) and 24 g of methylphosphoric acid were added to a reaction kettle, distilled water was added, stirred evenly, nitrogen was continuously introduced, a second catalyst was added, heated to 150°C for reaction for 3 hours, and cooled to 20°C after the reaction was completed to obtain a reaction solution. The second catalyst was a mixture of silicon chloride, magnesium chloride and aluminum trichloride, and the ratio of silicon chloride, magnesium chloride and aluminum trichloride was 1:1:1.
[0086] The obtained reaction liquid is separated to obtain an oil phase, and the oil phase is washed three times with 15° C. distilled water, separated, dehydrated, filtered, and distilled to obtain an antibacterial and antiviral nanomaterial of formula (I).
[0087] Figure 3 The infrared absorption spectrum of the antibacterial and antiviral nanomaterial of formula (I) prepared in Example 1 is as follows: Figure 3 As shown, 2970cm -1 and 2888cm -1is the stretching vibration absorption peak of saturated CH; 1537cm -1 is the stretching vibration absorption peak of CO; 1512cm -1 is the stretching vibration absorption peak of CN; 1236cm -1 is the absorption peak of P=O; 1030cm -1 It is the characteristic absorption peak of POC; 832cm -1 and 1315cm -1 It is the bending vibration absorption peak of P-CH3; 525cm -1 and 512cm -1 It is the stretching vibration absorption peak of Cu-O. The above conclusions confirm the appearance of each chemical bond of the product, and further prove the existence of the target product.
[0088] The textile samples treated with the organic flame retardant provided by the present invention are tested for antibacterial properties, antibacterial properties, heavy metal dissolution and flame retardant properties.
[0089] (1) The antibacterial performance evaluation refers to the national standard: "Oscillating method for evaluation of antibacterial properties of textiles GB / T 20944.3-2008".
[0090] Take 3 samples from the antibacterial fabric sample (each with a size of 10cm×10cm, cut into 2 pieces), wash according to the test condition A1M in GB / T 12490, and use ECE phosphorus-free standard detergent. Use water temperature 40℃±3℃, detergent concentration 0.2%, 150mL solution, 10 steel balls, and wash for 45min. After washing, take out the sample and wash it twice in 40℃±3℃ and 100mL water, 1min each time. Repeat this procedure until the specified number of washes. To prevent residual detergent from interfering with the antibacterial performance test, wash the sample thoroughly at the end of the last procedure, and then air or dry it.
[0091] Take 40 mL of E. coli solution prepared with PBS buffer, add the antibacterial and antiviral textile fabrics washed for different times and a blank sample, and culture at 37°C with shaking at 150 r / min for 18 hours. Use the nutrient agar plate method, count after culturing at 37°C for 24 hours, measure the concentration of E. coli and calculate the removal rate.
[0092] (2) Antiviral evaluation refers to the international standard: "Textiles - Determination of antiviral activity of textiles ISO 18184".
[0093] Take 40 mL of MS2 bacteriophage solution prepared with PBS buffer, add the above antibacterial and antiviral textile fabrics washed for different times and a blank sample, and culture at 37°C with shaking at 150 / min for 12 hours. Use the double-layer plate method, culture in a 37°C incubator for 6-8 hours, count, measure the MS2 bacteriophage concentration and calculate the removal rate.
[0094] The antibacterial and antiviral properties of the flame retardant are evaluated as follows: Figure 4 , Figure 5 As shown, after 6 washings, the test results are listed in Tables 1 and 2. The textiles added with the antibacterial and antiviral nanomaterials of the present invention still have an antibacterial effect of more than 90% and an antiviral effect of more than 85%. It can be seen that the antibacterial and antiviral effects are not easy to decay and are stable over time.
[0095] The special feature of the present invention is that the antibacterial and antiviral effect of the flame retardant is achieved by using the disinfection effect of copper ions. The antibacterial and antiviral nanomaterial synthesized by the steps of the present invention can give full play to the antibacterial effect of copper ions. It is worth mentioning that the chloride ions in the synthesized material also have a good disinfection effect, forming a synergistic effect with copper ions to make the antibacterial effect better. The preparation steps in the present invention can stably combine copper dichloroisocyanurate with organic phosphorus to form a product with stable physical and chemical properties, and still have a good antibacterial effect after multiple water washings.
[0096] Table 1 Effect of washing times on the antibacterial effect of textiles
[0097]
[0098]
[0099] Table 2 Effect of washing times on the antiviral effect of textiles
[0100]
[0101] (3) The heavy metal dissolution determination refers to the national standard: "Determination of heavy metals in textiles - Atomic absorption spectrophotometry GB / T 17593.1-2006".
[0102] Take a 5mm×5mm textile sample with antibacterial and antiviral properties synthesized using the organic flame retardant of the present invention, mix well, weigh two 4g samples (for parallel tests), accurate to 0.01g, and place them in a stoppered conical flask. Add 80mL of the prepared simulated acid sweat to fully wet the fiber, put it in a constant temperature water bath oscillator for 60 minutes, then take it out, let it stand and cool to room temperature, and filter it as a sample liquid for analysis.
[0103] Dilute the prepared copper standard working solution with water step by step to a series of working solutions of appropriate concentrations. At a wavelength of 324.7nm (Cu), use a graphite furnace atomic absorption spectrophotometer to measure the absorbance of copper in the series of working solutions in order from low to high concentrations, and draw a working curve with absorbance as the ordinate and concentration (μg / mL) as the abscissa. Determine the absorbance of each element to be measured in the blank solution and the sample solution, and calculate the concentration of each element to be measured from the working curve.
[0104] According to the requirements for the precipitation of heavy metal copper in the national standard Technical Requirements for Ecological Textiles GB / T 18885-2020, products that come into direct contact with the skin should be less than 50.0 mg / kg. As shown in the metal copper precipitation analysis results listed in Table 3, this antibacterial and antiviral nanomaterial can meet the precipitation requirements.
[0105] Table 3 Analysis of metal copper precipitation
[0106] sample Copper precipitation content Example 1 Textiles 2.15mg / kg Example 2 Textiles 2.71mg / kg Example 3 Textiles 3.54mg / kg
[0107] (4) Flame retardancy performance is measured with reference to the national standard: "Textiles - Determination of vertical combustion performance - Damage length, smoldering and afterflaming time GB / T 5455-2014".
[0108] Take a cloth with a size of 300mm×89mm, take 3 pieces in the warp (longitudinal) direction and 2 pieces in the weft (transverse) direction, for a total of 5 samples. Place the sample in an oven at (105±3)℃ and dry for (30±2)min, take it out and place it in a dryer to cool, the cooling time shall not be less than 30min. Place the sample in a vertical combustion tester to measure its afterflaming time, smoldering time and damaged length.
[0109] According to the combustion performance requirements of the national standard flame-retardant fabric GB / T 17591-2006, as shown in the flame retardant performance test results listed in Table 4, this flame retardant has a B1 grade flame retardant effect, and the amount of fabric per unit area is small and the flame retardant effect is good.
[0110] Table 4 Flame retardant performance determination
[0111]
[0112]
[0113] The textile samples synthesized by the organic flame retardant proposed in the present invention are tested for antibacterial performance, antibacterial performance, heavy metal dissolution and flame retardant performance. The experimental data show that the antibacterial and antiviral nanomaterial provided by the present invention has good antibacterial and antiviral performance. After 6 washings, it still has more than 90% antibacterial effect and more than 85% antiviral effect. Its antibacterial and antiviral effect is not easy to decay and has stability during use. The antibacterial and antiviral nanomaterial provided by the present invention has a small amount of copper precipitation, which can meet the precipitation requirements, has a B1-level flame retardant effect, and has a good flame retardant effect.
[0114] Those skilled in the art will appreciate that the above embodiments are merely examples, wherein features of different embodiments may be combined with each other to obtain implementation methods that are easily conceivable based on the contents disclosed in the present invention but are not explicitly indicated in the drawings.
[0115] It should be understood by those skilled in the art that the embodiments of the present invention described above and shown in the accompanying drawings are only examples and do not limit the present invention. The purpose of the present invention has been fully and effectively achieved. The functional and structural principles of the present invention have been demonstrated and explained in the embodiments, and the embodiments of the present invention may be deformed or modified in any way without departing from the principles.
Claims
1. A bacteriostatic and antiviral nanomaterial represented by formula (I) R-Cu-R (Ⅰ) 2. The method for preparing the antibacterial and antiviral nanomaterial according to claim 1, characterized in that: The preparation method comprises the following steps: S1: performing a replacement reaction between sodium dichloroisocyanurate and cupric chloride, and obtaining cupric dichloroisocyanurate by crystallization and filtration; S2: After adjusting the pH value of the ethanol aqueous solution, add the copper dichloroisocyanurate described in step S1 and mix, and react under the action of the first catalyst to obtain formula (C) R2-Cu-R2 (C) S3: reacting the formula (C) described in step S2 with methylphosphoric acid filled with nitrogen under the action of a second catalyst to obtain the antibacterial and antiviral nanomaterial of formula (I); The first catalyst is a substance formed by combining one or more of iridium, nickel, palladium, platinum, rhodium or ruthenium metals with activated carbon; The second catalyst is one or more of magnesium chloride, aluminum chloride and silicon chloride.
3. The preparation method according to claim 2, characterized in that: The preparation method has one or more of the following characteristics: In step S2, the reaction temperature is 70-85°C; In step S2, the pH value is adjusted to 5.3-6.
0.
4. The preparation method according to claim 2, characterized in that: In step S1, the mass ratio of sodium dichloroisocyanurate to cupric chloride is (1.6-2.5):(1-1.5); the reaction temperature of step S1 is 40-50° C., and the reaction time is 2-4 hours.
5. The preparation method according to claim 2, characterized in that: In step S2, the volume concentration of the ethanol aqueous solution is 70% to 78%.
6. The preparation method according to claim 2, characterized in that: The mass ratio of copper dichloroisocyanurate to the first catalyst in step S2 is 10:(3-5); the reaction time of step S2 is 2-4 hours.
7. The preparation method according to claim 2, characterized in that: Step S2 also includes recrystallization, cooling the reaction mixture obtained in step S2, adding hydrochloric acid to acidify and then filtering, dissolving the filtered product in a petroleum ether-ethanol mixed solution for recrystallization, wherein the molar ratio of petroleum ether to ethanol is (1-1.5): (0.5-1), and the temperature of the petroleum ether-ethanol solution is 60-70°C.
8. The preparation method according to claim 2, characterized in that: In step S2, the mass ratio of formula (C) to methyl phosphoric acid is (3.5-4.5):(9-12), the reaction temperature is 100-150° C., and the reaction time is 3-7 h.
9. The preparation method according to claim 2, characterized in that: In step S2, the first catalyst is added in 3 to 5 equal portions within a reaction time of 1 to 3 hours.
10. The preparation method according to claim 2, characterized in that: Step S3 also includes liquid separation and low-temperature water washing. The reaction liquid obtained in step S3 is separated to obtain an oil phase, and the oil phase is washed with low-temperature water. The water washing temperature is 10-15° C. and the number of water washings is 2-3 times.
Citation Information
Patent Citations
Cyanuric chloride derivative as well as preparation method and application in anti-wrinkle finishing agent of cyanuric chloride derivative and finishing method of pure silk fabric
CN102558078A
Cationic antimicrobial and preparation method and application thereof
CN102715170A